2005
DOI: 10.1111/j.1365-2958.2005.04918.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Klebsiella pneumoniae virulence determinants using an intranasal infection model

Abstract: SummaryKlebsiella pneumoniae is a Gram-negative enterobacterium that has historically been, and currently remains, a significant cause of human disease. It is a frequent cause of urinary tract infections and pneumonia, and subsequent systemic infections can have mortality rates as high as 60%. Despite its clinical significance, few virulence factors of K. pneumoniae have been identified or characterized. In this study we present a mouse model of acute K. pneumoniae respiratory infection using an intranasal ino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
225
2
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(242 citation statements)
references
References 52 publications
8
225
2
2
Order By: Relevance
“…Lawlor and colleagues demonstrated that CPS is a crucial component of the K. pneumoniae surface structure that is relevant to the internalization of this pathogen into epithelial cells (24). In our studies, K. pneumoniae showed significant internalization after 1 hour of infection, indicating that the infection is time-dependent and bacterial load-dependent.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Lawlor and colleagues demonstrated that CPS is a crucial component of the K. pneumoniae surface structure that is relevant to the internalization of this pathogen into epithelial cells (24). In our studies, K. pneumoniae showed significant internalization after 1 hour of infection, indicating that the infection is time-dependent and bacterial load-dependent.…”
Section: Discussionsupporting
confidence: 56%
“…Previously, isogenic capsule-negative strains (DCPS) showed higher adhesion to airway cells (24). Thus, we studied whether CPS also plays a role in the internalization and its relevance to lipid rafts.…”
Section: Raft-dependent Bacterial Internalization Is Enhanced By Delementioning
confidence: 99%
“…Similarly, wildtype Klebsiella pneumoniae, which can also cause an acute bacterial pneumonia, failed to significantly trans-complement isogenic strains that have mutations in predominant virulence genes (such as a ΔcpsB mutant, which lacks the polysaccharide capsule) or pCD1 − mutants of Y. pestis (Fig. 3B) (16). Conversely, virulent Y. pestis was able to significantly trans-complement ΔcpsB K. pneumoniae and fully trans-complement pYV − Y. pseudotuberculosis IP2666c (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Hospitalized or elderly patients with K. pneumoniae infections are at great risk of dying, with reported mortality rates of between 25% and 60% (Lawlor et al 2005). S. pyogenes is also a known cause of morbidity and mortality in humans and is responsible for both respiratory tract infections and invasive diseases (Musher 1992;Reinert et al 2004).…”
Section: K Pneumoniae and S Pyogenes Are Importantmentioning
confidence: 99%